The impact of flooding on Nigeria’s sustainable development goals (SDGs) - Adaku Jane Echendu (Taylor & Francis Group, 2020)
Nigeria has Africa’s biggest economy and a population of over 200 million people. Nigeria faces numerous challenges as it struggles to achieve the Sustainable Development Goals (SDGs) with flooding being the most serious with wide-reaching impacts. This paper highlights the impact flooding has on Nigeria reaching SDGs and enumerates the specific SDGs most directly impacted. A systematic literature review provides an overview of the relationship between flooding in Nigeria and the SDGs. It highlights the main causes of Nigeria’s flooding problem are man-made and advocates spatial planning as a suitable Flood Risk Management (FRM) strategy for the Nigerian environment. The paper calls for collaborative action by all concerned stakeholders to address the flooding problem and to help move Nigeria closer to meeting the United Nations (UN) 2030 SDGs. Most importantly, the evidence presented in this paper seeks to promote action on a national scale to combat the flooding in Nigeria and help the nation work more effectively toward achieving the SDGs.